2013
DOI: 10.1177/1933719112459227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Angiogenic Factors, Antagonists, and Podocyte Injury on Development of Proteinuria in Preeclampsia

Abstract: Proteinuria is universal to all patients with preeclampsia. We examined the urinary podocytes in women with preeclampsia (n ¼ 14), gestational hypertension (n ¼ 14), and normal pregnancy. Maternal serum and urinary concentrations of vascular endothelial growth factor (VEGF), placental growth factor (PlGF), and the antiangiogenic factor soluble fms-like tyrosine kinase 1 (sFlt-1) were detected. These concentrations were used to evaluate the urinary excretion of podocytes and the alteration of angiogenic factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 41 publications
1
22
0
2
Order By: Relevance
“…170 In another study, the number of urinary podocytes (identified by immunostaining for podocalyxin) per millilitre of urine correlated with total urinary protein, systolic and diastolic blood pressure, and was inversely correlated with both free PlGF and the PlGF to sVEGFR-1 ratio at the time of diagnosis of pre-eclampsia. 170,171 These observations strengthen the evidence supporting an imbalance between angiogenic and antiangiogenic factors and podocyte injury as having a role in development of the clinical features of pre-eclampsia.…”
Section: An Antiangiogenic Statesupporting
confidence: 59%
“…170 In another study, the number of urinary podocytes (identified by immunostaining for podocalyxin) per millilitre of urine correlated with total urinary protein, systolic and diastolic blood pressure, and was inversely correlated with both free PlGF and the PlGF to sVEGFR-1 ratio at the time of diagnosis of pre-eclampsia. 170,171 These observations strengthen the evidence supporting an imbalance between angiogenic and antiangiogenic factors and podocyte injury as having a role in development of the clinical features of pre-eclampsia.…”
Section: An Antiangiogenic Statesupporting
confidence: 59%
“…9,10,20 Previous studies evaluating the pathogenesis of proteinuria in preeclampsia have demonstrated pathogenic mechanisms including down-regulation of podocyte expression of nephrin, increased endothelin and decreased vascular endothelial growth factor (VEGF), indicating a mechanism where the endothelium loses its fenestrations, an alteration which contributes to protein loss in the urine. [29][30][31][32] Likewise, experimental models demonstrated that locally produced ANG II in the kidney may induce proteinuria via reduction of nephrin expression and podocyte injury and stimulated expression of some cytokines such as VEGF. [33][34][35] These findings suggest that local RAS activation in kidney may contribute to the pathogenesis of proteinuria in women with preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…102 Finally, in most studies PlGF is a more sensitive and precise predictor of preeclampsia and FGR than any other single biomarker. [103][104][105][106] Biomarkers that are predominantly maternal in origin (such as inflammatory cytokines or angiotensin II Type I receptor-autoantibodies; see Other Potential Biomarkers for Redefinition of Preeclampsia) would be expected to reflect maternal not placental pathophysiology of preeclampsia and for this reason are not the focus of this review.…”
Section: Redefining Preeclampsia Using Circulating Trophoblast-derivementioning
confidence: 99%